2023
DOI: 10.1021/acsaem.2c02998
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction of Metal Plasmas and CoO Nanofilms for Ultraefficient Activity to Oxygen Evolution Electrocatalysts

Abstract: Hydrogen production by electrolysis of water is expected to be one of the important technologies for sustainable clean energy production, but the sluggish kinetics of the oxygen evolution reaction (OER) hampers commercialization. The atomic layer deposition and high-energy metal plasma implantation were used to construct heterostructures of CoO with different thicknesses and multiple metals. Among them, the heterostructure constructed by cobalt oxide and Zr metal shows better oxygen evolution catalytic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…[39] Wang's research group used atomic layer deposition and high-energy metal ion implantation techniques to fabricate CoO heterostructures with different metal thicknesses. [40] The results showed that metal-semiconductor heterojunctions exhibited enhanced barrier heights and increased electron-hole pairs, leading to a higher positive charge density on the metal surface. This facilitated the adsorption of OH À ions and significantly improved the water splitting efficiency.…”
Section: Plasma Synthesis and Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] Wang's research group used atomic layer deposition and high-energy metal ion implantation techniques to fabricate CoO heterostructures with different metal thicknesses. [40] The results showed that metal-semiconductor heterojunctions exhibited enhanced barrier heights and increased electron-hole pairs, leading to a higher positive charge density on the metal surface. This facilitated the adsorption of OH À ions and significantly improved the water splitting efficiency.…”
Section: Plasma Synthesis and Conversionmentioning
confidence: 99%
“…successfully fabricated 1T/2H MoS 2 heterostructures using nitrogen plasma technology at room temperature, demonstrating excellent electrochemical hydrogen evolution reaction (HER) properties [39] . Wang's research group used atomic layer deposition and high‐energy metal ion implantation techniques to fabricate CoO heterostructures with different metal thicknesses [40] . The results showed that metal‐semiconductor heterojunctions exhibited enhanced barrier heights and increased electron‐hole pairs, leading to a higher positive charge density on the metal surface.…”
Section: Application Of Plasma Technology In Energy Storagementioning
confidence: 99%
“…[53,54] The better Li diffusion has already been observed in such hybrid electrolytes. [55] There is a gap in understanding of the diffusion property improvements brought about the confinement and the role of the solid-to-liquid interface in PVDF-based ionogels. [56,57] The present study aims to compare the ions dynamics in Li and Mg-doped ionic liquids and PVDFbased ionogel electrolytes to obtain information about the effect of salt addition and of confinement on the dynamics in salt-doped ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, developing inexpensive, stable, and highly efficient catalysts for the OER is still extremely needed. Based on this, non-noble metals such as carbides, 9,10 phosphides, 11,12 nitrides, 13,14 oxides, 15,16 hydroxides, 17,18 and sulfides 19,20 have been extensively studied and applied in the OER.…”
Section: Introductionmentioning
confidence: 99%